Pengaruh Minat Belajar Menggunakan Media Pembelajaran Komik Strip Terhadap Hasil Belajar Siswa Pada Materi Dampak Sosial Informatika di SMAN 6 Gorontalo Utara - Bonde, Masita; Novian, Dian; Suwandi, Ihsanulfu’ad (Universitas Lampung, 2024)
This research aims to develop comic strips as a teaching medium to help students increase their interest in learning and their influence on student learning outcomes in Social Impact of Informatics (DSI) material by creating comic strips containing content that can visualize the content of the material. The method used in this research is the Research and Development (R & D) development method with the Analysis, Design, Development, Implementation and Evaluation (ADDIE) model with the feasibility results of material experts showing a percentage of 100% with the category